Development and application of a methodology for selection of technological products suppliers (2012)
ln market globalization, it becomes important to dispose of a suitable tool that can allow finding the best supplier. It is especially important when it is about technological products. These kinds of products deserve a special treatment due to their own complexity and even complexity of the process that they are involved in. In this paper we present a new methodology for supplier selection that takes account the special characteristics of technological products. It is defined the structure of the methodology and all the parameters used to implement it. As confirmation of validity of the methodology, we show an example of application.